Representation of Regency Era in 'Emma' (2020) Movie: a Sociological Perspective - Sari, Yuliana Kartika; Amalia, Syahara Dina (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This research aims to analyze: (1) how the Regency Era is represented in the Emma (2020) movie and (2) to what extent the Regency Era influences the characters in the Emma movie from the sociology perspective. This research type is qualitative research using descriptive method. The data source was taken from the dialogues and scenes of the movie, as well as relevant sources such as relevant journals and websites. The data collection techniques used are document analysis and image-capturing. Sociological theory is used for data validation. The data analysis technique used is data reduction, data view and verification (Miles and Huberman, 1994). The results of this study are as follows. The representation of life in Emma movie based on the Regency era can be described in several ways, such as: costumes and fashion, architecture, social customs and manners, class distinctions, as well as romantic themes that used in the Emma movie is in accordance with the reality in the Regency Era.In addition, it was found that Regency Era influences the characters in Emma movie seen from sociological theory resulting in the characters of Emma, Harriet, Mr. Knightley and Mr. Robert Martin who influenced Regency Era.